Análise do comportamento do desgaste de dressadores de ponta única confeccionados com diamantes naturais e sintético piramidais - Hildebrandt, Rodolfo Alexandre [UNESP] (2014)
The dressing is an integral step in the grinding process, which is an operation of grinding, in other words, the rectification of the wheel, which has as main purpose the removal of worn abrasive grains and ensure concentricity of the wheel. In this context, this operation becomes more important in the performance of the wheel, and the quality of this process. These tests suggest the analysis of wear behavior and the life of the single point dresser, this step is very common in conventional grinding wheels where periodically the working face must be restored. In this work three types of diamonds are evaluated, one synthetic and two natural, where the data collected from the test will be recorded and achived for evaluation of initial and sequential values of the levels proposed for the removal of image being tabulated and further analyzed the relationship between the wear and lifetime of the worn areas for models of natural diamonds of type Extra Brazil and Mato Grosso. Already the National CVD Synthetic type showed a value of close to Brazil Extra abraded area. To the process, natural diamonds showed great variation in their structure and hardness, chipping occurring small when compared to the synthetic which presented a more consistent hardness at high temperatures without suffering and chipping during rehearsals. Based on the data obtained in this study, the National CVD Synthetic Diamond type showed a great advantage in durability compared to the other two diamonds tested, obtaining an equivalent type Brazil Extra wear. The Mato Grosso type showed a much lower quality in all aspects compared to the other